The Minimum Wage Revisited in the Enlarged EU - Vaughan-Whitehead, Daniel (Edward Elgar Publishing, 2010)
This book provides in-depth and innovative analysis of the minimum wage in Europe. The authors explore its role and scope within the enlarged EU, and address the question of whether there should be harmonization between the individual member states or even a common EU minimum wage. They also examine the impact of the minimum wage at the national level, looking at trends and effects through case studies of specific policy issues and industrial sectors. Minimum wage fixing has returned quite prominently to the core of policy debates as evidenced by the adoption of a statutory minimum wage in Ireland and the UK, a minimum wage agreement in Austria and the ongoing discussions in Germany and Sweden. Proposals to have common rules at the EU level have also multiplied since enlargement, in particular to minimize 'social dumping' and allow increased transnational mobility. This book assesses the renewed interest in the minimum wage in Europe, identifying the concrete effects of minimum wage fixing on employment, low pay, wage disparity, collective bargaining and migration. Bringing together 15 national studies from noted European specialists in the field, this timely collection aims to stimulate the current debate. It will appeal to academics, students, researchers and policymakers working in labour economics in particular, and European studies more generally.